Small-bodied males invest in larger testes when highly ornamented - De Souza, André Rodrigues; Polo, João Lucas Lapria; Santos, Eduardo Fernando [UNESP]; Nascimento, Fábio Santos do; Rantala, Markus J. (Oxford University Press (OUP), 2024)
Sperm competition and male mating rate are two non-mutually exclusive key evolutionary pressures selecting for larger testes within and across animal taxa. A few studies have tried to test the role of mating rate in the absence of sperm competition. Under the mating rate hypothesis, particular phenotypes of a given population that are expected to gain more mates (e.g., more ornamented males) are expected to make higher investments in testes size (a proxy for sperm production). We test this prediction in Polistes simillimus, a neotropical paper wasp in which females are single mated (no sperm competition) and males can mate with multiple partners. Testes size was predicted by body size (positive association), sexual ornamentation (negative association), and their interaction (among small males, testes size was positively related to ornamentation, but the opposite pattern was observed among large males). We propose that small-bodied well-ornamented males may face the highest risk of sperm depletion. Small-bodied males make relatively higher investment in testes size when highly ornamented. This strategy might be less profitable to large males, as they have overall larger testes. Our results provide strong evidence for the mating rate hypothesis.
Keywords: body size; mating rate hypothesis; sexual ornamentation; sperm depletion; testes size